Supply Chains and Antitrust Governance - Jain, Nitish; Hasija, Sameer; Netessine, Serguei (Management Science, 2021)
Antitrust regulations are meant to promote fair competition in the market, but balancing administrative and legal costs with enforcement can be difficult when multilayered supply chains are involved. The canonical example of this challenge is the landmark Illinois Brick ruling, which limits antitrust damages to only the direct purchasers of a product; for instance, consumers can file antitrust claims against colluding retailers but not against colluding manufacturers—only retailers can file claims against manufacturers. This controversial ruling was meant to reduce legal costs, but it can clearly lead to missed enforcement opportunities. In this paper, we demonstrate how the Illinois Brick ruling interacts with contracts adopted in the supply chain, and we show that otherwise equivalent supply chain arrangements can have markedly different effects. In particular, we find that wholesale price, minimum order quantity, revenue sharing, and quantity discount contracts lead retailers to take legal action against manufacturers in the event of collusive behavior. However, the wholesale price plus fixed fee contract structure (also known as a two-part tariff or slotting fee contract) facilitates collusion among the manufacturers with retailers compensated by the fixed fee and not filing the antitrust litigation. We further demonstrate that collusion is more likely under high demand uncertainty and high competition at the retail level but is less likely under high competition at the manufacturer level. Our paper helps public enforcers identify market conditions conducive to antitrust violations. This paper was accepted by Vishal Gaur, operations management.